Viral factors of poxviruses and coronaviruses that suppress host gene expression - Molina, Joshua (Kansas State University, 2022)
Host shutoff is the phenomenon observed when many viruses downregulate host cellular gene expression resulting in a global suppression of nascent protein production. A virus can encode multiple factors that interfere at different stages of gene expression from transcription, mRNA processing and export, to translation. While much work has been done to define those viral factors that induce host shutoff, more needs to be done to fully characterize those host shutoff factors and identify novel host shutoff factors that could potentially elucidate previously unknown mechanisms underlying viral-host interactions. The development of innovative techniques will improve our ability to elucidate novel mechanisms involved in viral host shutoff. The work in this dissertation addresses this by developing of a novel high throughput assay that allows for rapid, quantitative, and consecutive monitoring of host shutoff and also studying viral host shutoff factors and screening for previously unknown host shutoff factors. Our results demonstrated high-throughput assay utilizing a cell line stably expressing Gaussia luciferase could be used to analyze host shutoff from a single VACV infected sample quantitatively and in real time. Utilizing the Gaussia assay, our results showed the strongest inhibition of protein synthesis during VACV infection came from post-replication of the viral genome. We also showed VACV was able to induce host shutoff while encoding inactive/deleted decapping enzymes, suggesting other late gene viral factors may contribute to host shutoff. Next, we developed a VACV late gene screening assay to identify additional viral late genes that contributed to host shutoff. The results from this screening identified eight late genes that were possibly capable of inducing host shutoff, a function not previously defined for these genes. Coronavirus disease 2019 is a respiratory illness caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Multiple vaccines and therapies have been developed to mitigate the risk of this disease to the public, but a better understanding of the virus and its pathogenesis will allow for improved treatments for the current and future coronavirus pandemics. The work in this dissertation addressed this by characterizing the host shutoff factor nsp1 of SARS-CoV-2 and performed a screening to find other viral genes of SARS-CoV-2 that contribute to host shutoff. Our results show nsp1 is capable of inducing host shutoff, and residues R124 and K125 in the N-terminal, residues K164 H165 in the C-terminal, and residues 122-130 are critical for nsp1 SARS-CoV-2 host shutoff function. We then screened all the SARS-CoV-2 viral genes for their ability to induce host shutoff utilizing our EF1a-Gaussia luciferase reporter plasmid and showed that some structural and accessory proteins were potentially capable of inducing host shutoff as well as nsp5, the SARS-CoV-2 viral proteinase. Taken together, this work develops new tools that can be used to study protein synthesis suppression by viral infection and other physiologically relevant stresses, as well as identifies new viral host shutoff factors; both of which contribute to the current understanding of virus-host interactions.
Keywords: Gaussia luciferase; Host shutoff; Poxvirus; Reporter cell line; Vaccinia virus